Evaluasi Keamanan E-Office Desa Menggunakan Indeks Kami: Studi Kasus DISKOMINFO Kab. Sumedang - Faridz Muhamad Permana; Fidi Supriadi; Dani Indra Junaedi (STIKes Ibnu Sina Ajibarang, 2025)
Evaluating system security is a crucial step in preventing data breaches and application disruptions. This research focuses on evaluating the security of the E-Office Desa application in Sumedang Regency using the Indeks KAMI as its assessment method. Indeks KAMI is designed to measure the maturity level and effectiveness of information security management within an organization. The data processed was collected from questionnaires distributed to village officials in Sumedang Regency. This evaluation covers six main domains: Governance, Risk Management, Information Security Framework, Asset Management, Information Technology and Security, and Personal Data Protection. Based on the analysis of the data obtained from the questionnaire distribution, the security level of the E-Office Desa application in Sumedang Regency is at maturity level III, which indicates